2020
DOI: 10.1002/agj2.20032
|View full text |Cite
|
Sign up to set email alerts
|

Risk and returns from grazing beef cattle on warm‐season grasses in Tennessee

Abstract: Beef cattle production in the southeastern United States is forage‐based, relying primarily on tall fescue (Schedonorus arundinaceus [Schreb.] Dumort; TF). While TF has many desirable characteristics for forage, physiological traits can create forage management challenges for producers during the summer. Managing forage production is necessary for producers to maximize profits and reduce feed costs. A possible way to extend grazing in this region is to use warm‐season grasses (WSGs) during summer to complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…In another economic analysis, EG outperformed a summer annual [crabgrass, Digitaria ciliaris (Retz.) Koeler] in terms of net returns for grazing weaned beef heifers (Boyer, Zechiel, Keyser, Rhinehart, & Bates, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another economic analysis, EG outperformed a summer annual [crabgrass, Digitaria ciliaris (Retz.) Koeler] in terms of net returns for grazing weaned beef heifers (Boyer, Zechiel, Keyser, Rhinehart, & Bates, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of SXS, high forage yields, 7–10 Mg ha −1 , can be produced at a time of year when TF has become semi‐dormant and is not productive (Fontaneli, Sollenberger, & Staples, 2001; Machicek, Blaser, Darapuneni, & Rhoades, 2019). However, these summer annuals are less cost‐effective (Boyer et al., 2019; Keyser, Bates, Waller, Harper, & Holcomb, 2015; Tracy et al., 2010), may not be available in early summer (Tracy et al., 2010; Zechiel, 2017) and thus provide fewer grazing days (Zechiel, 2017) than perennials.…”
Section: Introductionmentioning
confidence: 99%
“…); LB], and eastern gamagrass [ Tripsacum dactyloides (L.) L.]. Native warm‐season grasses are low input, endophyte free, persistent, productive during summer, and drought tolerant (Anderson, 2000; Boyer, Zechiel, Keyser, Rhinehart, & Bates, 2020; Keyser, Bates, Waller, Harper, & Doxon, 2012; Keyser, Harper, Bates, Waller, & Doxon, 2011; Lowe et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Transport to the farm adds a constant footprint of 0.106 kg of CO 2 eq./kg of material moved from regional warehouses to farms except for poultry manure [16]. 4 Taken from Rotz et al [17]. 5 Cost information for fuels and fertilizer were sourced from archived cost of production information provided by Mississippi State University [18].…”
Section: Partial Lifecycle Assessmentmentioning
confidence: 99%
“…Estimating economic and sustainability impacts of introducing switchgrass (Panicum virgatum L.; SG) for making hay and supplying SG biomass to biorefineries while holding the cattle output constant is thus the focus of this analysis. Previous work, assessing the extent to which SG could be used profitably for grazing has found that, at a sufficiently high price for biomass, grazing-only and mechanical harvest for biomass after grazing could improve profitability [4,5]. Furthermore, cattle performed well on SG, and SG was economically optimal in comparison with other native warm-season grasses.…”
Section: Introductionmentioning
confidence: 99%